Nonlinear Three Point Boundary Value Problem - Guezane-Lakoud, A.; Frioui, A. (Sarajevo Journal of Mathematics, 2024)
In this work, we establish sufficient conditions for the existence of solutions for a three point boundary value problem generated by a third order differential equation. We give sufficient conditions that allow us to obtain the existence of a nontrivial solution. Then by using the Leray Schauder nonlinear alternative we prove the existence of at least one solution of the posed problem. As an application, we give two examples to illustrate our results. 2000 Mathematics Subject Classification. 34B10, 34B15, 34B18, 34G20